2010
DOI: 10.1037/a0020182
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal examination of the parent–child distress relationship in children with juvenile rheumatic disease.

Abstract: Objective: To examine the longitudinal relationships between parent and child distress in a sample of children with juvenile rheumatic diseases (JRDs). Design: Cross-lagged panel correlation analysis tested the temporal precedence of parent distress versus child distress over a 1-year period. Participants: Thirty-seven children (ages 9–17 years; 22 girls) diagnosed with JRD and their parents completed self-report measures on 2 occasions (assessment interval M = 12 months). Primary Outcome Measures: Child Depre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
14
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 74 publications
(137 reference statements)
4
14
1
Order By: Relevance
“…Second, the sample of fathers included were primarily married, highly educated, relatively affluent, Caucasian men; thus, it should be noted that these findings may not generalize to all populations. Third, although parental psychopathology is salient to parenting practices and child adjustment outcomes (Kazak & Barakat, 1997;Ryan et al, 2010), examination of this factor was outside of the scope of this study, which specifically focused on the relation between paternal parenting variables and child uncertainty. Moreover, we acknowledge that conducting three separate regression analyses may have increased the Type 2 error rate; however, this statistical approach was chosen due to the preliminary nature of this study and the limited sample size of fathers.…”
Section: Discussionmentioning
confidence: 98%
“…Second, the sample of fathers included were primarily married, highly educated, relatively affluent, Caucasian men; thus, it should be noted that these findings may not generalize to all populations. Third, although parental psychopathology is salient to parenting practices and child adjustment outcomes (Kazak & Barakat, 1997;Ryan et al, 2010), examination of this factor was outside of the scope of this study, which specifically focused on the relation between paternal parenting variables and child uncertainty. Moreover, we acknowledge that conducting three separate regression analyses may have increased the Type 2 error rate; however, this statistical approach was chosen due to the preliminary nature of this study and the limited sample size of fathers.…”
Section: Discussionmentioning
confidence: 98%
“…Child well-being-Physical/health status Active Joint Count for Disease Severity (developed for study; multiple indicators) Child Activity Limitations Questionnaire (Hainsworth, Davies, Khan, & Weisman, 2007;Palermo, Lewandowski, Long, & Burant, 2008) Childhood Health Assessment Questionnaire (Ruperto et al, 2001) Disease Activity Index (Varni, Thompson, & Hanson, 1987) Faces Pain Rating Scale (Bieri, Reeve, Champion, Addicoat, & Ziegler, 1990) Functional Disability Inventory (Walker & Greene, 1991) Juvenile Arthritis Functional Assessment Report-Parent (Howe et al, 1991) Pain Status-Visual Analogue Scale (McGrath et al, 1996;Palermo, Valenzuela, & Stork, 2004) Structured Pain Questionnaire (King, Wold, Tudor-Smith, & Harel, 1996) (Andrews et al, 2009;Ramsey et al, 2013;Ryan et al, 2010;Wagner et al, 2003;White et al, 2005) Children's Depression Inventory (Andrews et al, 2009;Ramsey et al, 2013;Ryan et al, 2010;Wagner et al, 2003;White et al, 2005) Children's Uncertainty in Illness Scale (White et al, 2005) Juvenile Arthritis Functional Assessment Report (Andrews et al, 2009;Ryan et al, 2010;Wagner et al, 2003;White et al, 2005) Illness Intrusiveness Scale (Wagner et al, 2003) Children's Attributional Style Questionnaire-Revised (Ramsey et al, 2013) Caregiver Burden Scale (Bruns, Hilário, Jennings, Silva, & Natour, 2008) Childhood Health Assessment Questionnaire (functional status)…”
Section: Child Well-being Measures-psychological and Behavioralmentioning
confidence: 99%
“…Kazak, Segal-Andrews, and Johnson's (1995) social-ecological model states that parent and child adjustment to a chronic illness is closely tied and is a result of the complex interaction among parent, child, illness, and demographic factors. As such, these researchers state that parent adjustment can exert a significant effect on subsequent child adjustment (e.g., Ryan et al, 2010). Research has suggested this theory to be correct, with both cross-sectional and longitudinal studies across multiple chronic illness populations, including youth with JRDs, demonstrating the robust association between parent adjustment and child and adolescent adjustment difficulties (e.g., Chaney et al, 1997;Mullins & Chaney, 2001;Thompson, Gustafson, Gil, Kinney, & Spock, 1999;Wagner et al, 2003).…”
Section: Introductionmentioning
confidence: 99%